Uma análise discursiva de ditos e escritos de/sobre Pedro Casaldáliga - Melo, Andréia Cristina André Soares (2020)
ABSTRACT: In this thesis, inscribed in the area of Discourse Studies, affiliated to the theory of the analysis of the basic enunciative-pragmatic discourse (Maingueneau), we have the purpose of analyzing: how is the image of author constituted from the sayings and writings of/on Don Pedro Casaldáliga? Researchers of literary theory for decades have been studying the works (poems) of the author, instituting to him a place, a space, a time in the literature and images of (engaged poet, founder/theorist of casaldalian poetry); other areas of knowledge (human sciences), go through the archives with the objective of constituting a narrative about the life of the Bishop, "the causes that imprint his life," leading to the "discovery" of the author's identities, which in the process, in the face of discursive materialities, elsewhere, figure and configures the author images of author-person (militant, humanist, prophetic), based on praxis. Starting from the assumption that the image of author is not only a product, a multiform activity of the author, result of his text, but, constituted in the confluence of his gestures on one side, of the words of the various audiences on the other, we base our analysis on some theoretical-conceptual assumptions, as of the instances (person, writer, inscriber) and dimensions of regulation and figuration (MAINGUENEAU, 2010), of the notion of author as a "function-author" (FOUCAULT, 2001), we are reflecting the means by which certain images of author are built for D. Pedro Casaldáliga; therefore, to what extent does the image of author in the paratext (preface, titles, author's name) establish D. Pedro an author function? To answer this question it was necessary to reflect on the notion of author (BARTHES, 2004); (FOUCAULT, 2001), without first visiting the notion of work and its literary context (MAINGUENEAU, 2016). The notion of function-author (Foucault, 2001), will be contextualized with the notions of interdiscursive competence, constituent discourse and scene of enunciation that allowed us to reflect, in confluence with the theories of enunciation (Benveniste, Ducrot), the images of author (previous), with the image of author La Proleta, conceived by us. The notion of archive (FOUCAULT, 2001) and discursive event (GUILHAUMOU, 2009; GUILHAUMOU; MALDIDIER; ROBIN, 2016) was fundamental for the constitution of the corpuss, since we organized them from various discursive materialities: dissertations, biography, interview, preface, magazine cover, fragments of the author's works and letters. To reflect on the image of the author it is necessary to analyze it in its entirety (FIORIN, 2015).